ANALISIS DAN PERANCANGAN SISTEM INFORMASI MANAJEMEN KERJASAMA PADA SETDA PEMERINTAHAN KABUPATEN BANYUWANGI - Made Asri Syaiba Almihda Hasan; Abd. Ghofur; Hendri Nawawi (CV. Denasya Smart Publisher, 2025)
B Banyuwangi Regency, as one of the regions with a strong commitment to the implementation of the Electronic-Based Government System (SPBE), has developed a Cooperation Sub-Section within the Banyuwangi Regency Regional Secretariat. The system functions to record, manage, and report cooperation data with both internal and external stakeholders. Although it has contributed to the digitization of administration, the system still has several limitations, particularly regarding its outdated user interface and the absence of an online cooperation submission feature. As a result, the process remains partly manual and less efficient. Based on these conditions, this research focuses on analyzing, designing the interface, adding online-based cooperation submission features, and providing more integrated monitoring features. The research employs the System Development Life Cycle (SDLC) method using a prototype model. It is expected that the resulting system design will be more modern, professional, interactive, and user-friendly, thereby improving the quality of public services, enhancing the government’s digital image, and supporting transparency within the Banyuwangi Regency Government.